2020
DOI: 10.2169/internalmedicine.4016-19
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Insufficient Optimal Medical Therapy after Acute Myocardial Infarction

Abstract: Objective Although the importance of evidence-based optimal medical therapy (OMT) after acute myocardial infarction (AMI) has been recognized, the prescription rate of OMT is not sufficiently high in real-word clinical settings. The purpose of this study was to identify the clinical characteristics of AMI patients who did not receive OMT. Methods The present study was a retrospective study. OMT was defined as the combination of antiplatelet therapy, angiotensin-converting enzyme (ACE) inhibitors/angiotensin II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…They demonstrated advanced age, impaired renal function, vasospastic angina, bradycardia, asthma, non-PCI revascularization, and NSTEMI that were significantly associated with non-OMT. 11 Yan et al examined the use of medications at discharge among 5833 patients from the Canadian ACS I and ACS II Registries. Advanced age, female sex, prior heart failure, renal function, and coronary bypass surgery were shown to be negative independent predictors of OMT.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated advanced age, impaired renal function, vasospastic angina, bradycardia, asthma, non-PCI revascularization, and NSTEMI that were significantly associated with non-OMT. 11 Yan et al examined the use of medications at discharge among 5833 patients from the Canadian ACS I and ACS II Registries. Advanced age, female sex, prior heart failure, renal function, and coronary bypass surgery were shown to be negative independent predictors of OMT.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor Haraguchi et al showed that several baseline characteristics were associated with the failure of optimal medical therapy, including anti-platelets, angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers, beta-blockers, and statins, at the time of index discharge following acute myocardial infarction ( 1 ). Their findings may help improve the strategy for increasing the rate of delivering optimal medical therapy following acute myocardial infarction.…”
mentioning
confidence: 99%
“…The Authors Reply We appreciate the constructive comments made by Dr. Imamura regarding our manuscript (1). First, we did not exclude patients with acute myocardial infarction (AMI) caused by vasospastic angina from our study population.…”
mentioning
confidence: 99%